Strategies for the Management of Traditional Chestnut Landscapes in Pesio Valley, Italy: A Participatory Approach - Paola Gullino; Maria Gabriella Mellano; Gabriele Loris Beccaro; Marco Devecchi; Federica Larcher (Land, 2020)
Through an exploratory case study conducted in the Pesio Valley, northwest Italy, this paper proposes a framework for maintaining traditional chestnut production landscapes and addressing future development policies. The main goal was to understand how to promote a bottom-up planning approach, including stakeholder perceptions in traditional chestnut landscape management. To ensure the sustainability of the landscape, current driving forces and their landscape effects were identified by local stakeholders using a focus group technique. Population ageing, local forestry policies directed towards supporting chestnut growers’ income, social and economic needs, and land fragmentation are the main driving forces that will influence future chestnut landscapes. The focus group participants built two scenarios of possible future development of the chestnut landscape, one characterized by the disappearance and transformation of chestnut stands, the other by their permanence and maintenance. The most recommended strategies for maintaining traditional chestnut cultivation were chestnut processing, fruit designation of origin, and the cultivation of traditional varieties. This study shows that, to preserve the traditional chestnut landscape, the participation of multiple stakeholders is a useful approach in landscape planning. This methodology could guide decision-makers and planners who desire to implement a participatory approach to a sustainable development program for traditional chestnut landscapes.